Finding a balance between academic freedom and university autonomy. Some reflections on the cases of Poland and Slovakia (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
Academic freedom, freedom of expression and university autonomy are core values that ensure the well-functioning of higher education. Both Poland and Slovakia do comply with international and European standards on academic freedom. However, recent reforms on higher education – adopted in Poland and debated in Slovakia – are putting a strain on the freedom of teaching personnel and institutional autonomy. The analysis will shed some light on the different impact of the reforms introduced in these two countries to address similar challenges.
Keywords: Academic Freedom; University autonomy; Reform of the Higher Education; Poland; Slovakia